2011
DOI: 10.1248/cpb.59.1425
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phenolic Constituents from the Seeds of Pharbitis nil

Abstract: Two new lignans, termed pharsyringaresinol (1) and pharbilignoside (2), a new phenylethanoid glycoside, termed pharbiniloside (3), and 22 known compounds, were isolated from the ethanol extract of the seeds of Pharbitis nil. The structures of the new compounds (1-3) were determined on the basis of spectroscopic analyses, including 2D-NMR and circular dichroism (CD) spectroscopy studies. Among the isolates, compounds 2, 11, 12, and 24 exhibited significant cytotoxicity against human tumor cell lines (A549, SK-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…4−8 Previously, we found that an ethanol extract of the seeds of morning glory (Pharbitis nil) exhibited considerable cytotoxicity against A549, SK-OV-3, SK-MEL-2, and HCT-15 human tumor cell lines in our screening test and reported several cytotoxic phenolic constituents including lignans from ethanol (EtOH) extracts. 8 Morning glory (Convolvulaceae) is a famous flower that is popular as an ornamental plant. The seeds of P. nil (Pharbitidis Semen) is both a food and a medicinal agent that has traditionally been used as a purgative in Korea, China, and Japan.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4−8 Previously, we found that an ethanol extract of the seeds of morning glory (Pharbitis nil) exhibited considerable cytotoxicity against A549, SK-OV-3, SK-MEL-2, and HCT-15 human tumor cell lines in our screening test and reported several cytotoxic phenolic constituents including lignans from ethanol (EtOH) extracts. 8 Morning glory (Convolvulaceae) is a famous flower that is popular as an ornamental plant. The seeds of P. nil (Pharbitidis Semen) is both a food and a medicinal agent that has traditionally been used as a purgative in Korea, China, and Japan.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11−13 However, to our knowledge, only our previous study has investigated the lignan phytochemicals of Pharbitidis Semen. 8 Presently, we used activity-guided fractionation combined with chromatography to focus on identifying antitumor lignan deriviatives from the seeds of morning glory. In this article, we describe the isolation and structural determination of four new lignans named pharbilignans A-D (1−4) ( Figure 1) as well as their biological activity with respect to cytotoxic and antiinflammatory activities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides the effects of Milkvetch Root on cardiovascular diseases, its effects on other diseases also have been reported, such as malignant plural effusion [14], diabetes [39, 40], and cancer [41]. Although Semen Pharbitidis is reported to has toxicology effect after long term administration [42], its therapeutic effect on relieving constipation by purgation, dispersing phlegm and washing excessive fluid is also well investigated, and is widely used for the treatment of edema, ascites, hydroncus, simple obesity, lung fever, tumor and ardent fever [4345]. Extraction of Semen Pharbitidis also shows antioxidant effect [46].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al isolated two phenylpropanoic acid derivatives, ( E )‐ethyl caffeate ( 35 ) and ( E )‐ p ‐ethyl coumarate ( 36 ), from the seeds of P. nil , which inhibited NO production in LPS‐activated BV‐2 cells with IC 50 values of 14.7 and 17.9 μM, respectively (K. H. Kim, Ha, Choi, Kim, & Lee, ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Kim et al isolated a series of lignans from the seeds of P. nil . Among them, pharsyringaresinol ( 44 ) and (−)‐syringaresinol ( 45 ) exhibit weak inhibitory effects against NO production in LPS‐activated BV‐2 cells (K. H. Kim, Ha, et al, ), whereas pharbilignan C ( 46 ) strongly inhibited NO production with an IC 50 value of 12.8 μM (K. H. Kim et al, ).…”
Section: Phytochemistrymentioning
confidence: 99%